(untitled) (Bangladesh Journal of Child Health, 2010)
Serum lactate dehydrogenase (LDH) level was estimated in 77 childhood (age range 1- 15 years) hemato-oncological malignancies: acute lymphoblastic leukemia (ALL), acute myeloid leukemia (AML), Hodgkin’s disease (HD) and Non- Hodgkin’s lymphoma (NHL) on admission. Serum LDH level was also measured in ALL on day 14 and day 29 of induction. Another 25 children without hemato-oncological malignancies were included as control. On admission, the level of serum LDH was significantly raised in all hematooncological malignancies but the levels was highly significant in ALL than control (p<0.001). Total WBC count was significantly decreased along with serum LDH level on day 14 and day 29 of induction (p<0.001). A significant rise of platelet count was observed on day 29 of induction in relation to significant decrease of serum LDH level (p<0.001). Significant decrease of peripheral and bone marrow blast cell percentages were also observed on day 29 of induction along with significant decrease level of serum LDH (p<0.001). It is observed in this study that serum LDH level was significantly elevated in all hemato-oncological malignancies on admission but the levels were highly significant in ALL patients. Following induction of remission in ALL, level of serum LDH was decreased along with the return of hematological parameters towards normal. So, the measurement of serum LDH level can be accepted as a predictor in diagnosis of hemato-oncological malignancies and prognosis of childhood ALL. Key words: Serum lactate dehydrogenase (LDH); Hemato-oncological malignancies; Induction; Acute lymphoblastic leukemia (ALL). DOI: 10.3329/bjch.v30i1.6175 Bangladesh J Child Health 2006; VOL 30 (1/2/3) : 1-6